2015
DOI: 10.1517/13543776.2015.1027192
|View full text |Cite
|
Sign up to set email alerts
|

1,2-Benzisoxazole compounds: a patent review (2009 – 2014)

Abstract: More recent examples of structural modification of existing drugs led to the discovery of some promising benzisoxazoles for antipsychotic use. The design of multi-target ligands is important for the manipulation of pharmacological properties and safety profiles for the use of antipsychotics. Benzisoxazoles have been widely used as pharmacophores in the search for novel drug candidates in a variety of therapeutic area. It is fair to assume that the wide and frequent use of benzisoxazoles in drug discovery and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…3). [39,40]. The heterocyclic ring structure of 1 shares similarity with the clinically used antibiotics cycloserine and linezolid.…”
Section: Molecular Docking Of 36-dihydroxy-12benzisoxazole Onto a mentioning
confidence: 97%
“…3). [39,40]. The heterocyclic ring structure of 1 shares similarity with the clinically used antibiotics cycloserine and linezolid.…”
Section: Molecular Docking Of 36-dihydroxy-12benzisoxazole Onto a mentioning
confidence: 97%
“…Because of their versatile properties and potential as selective ligands for a variety of macromolecular targets, these bicyclic aromatic ring systems constitute the essential structural motif in a wide range of pharmacologically active compounds, including a number of potential anticancer agents ( Figure 1 ) [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Furthermore, the benzisoxazole scaffold is often used as a bioisosteric replacement for the benzoyl group of biologically active molecules [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This approach takes two separate pharmacophores with distinct pharmacology and integrates them into one molecule with the attributes of both parent molecules. , The privileged structures from known antipsychotic drugs were covered (Figure ): (1) phenylpiperazines, which are known to be important motifs for the functional activity of antipsychotics, the preclinical and clinical tests demonstrated that compounds incorporating the 2,3-dichlorophenylpiperazine and 2-methoxyphenylpiperazine scaffolds are useful in the design of atypical antipsychotics, and (2) benzisoxazoles and benzoisothiazoles, which are important fragments, and some medications containing these moieties have been approved for human clinical use, including atypical antipsychotics (risperidone, paliperidone, ziprasidone, and lurasidone). The activities of the piperazine or piperidine moiety at D 2 and 5-HT 2A receptors followed by similar structural heterocycles have proven useful for antipsychotic efficacy . Moreover, the appropriate linker between the tricyclic heterocycles and the privileged structures is important for new compounds binding to the desired multireceptors (D 2 , D 3 , 5-HT 1A , 5-HT 2A , and 5-HT 6 receptors).…”
Section: Introductionmentioning
confidence: 99%